2017
DOI: 10.15448/1980-6523.2017.2.26330
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines in crevicular fluid and orthodontic force: a systematic review

Abstract: OBJECTIVE: This paper aimed to analyze studies in the literature addressing the role of cytokines in the gingival crevicular fluid (GCF) in the orthodontic treatment. METHODS: Several databases were surveyed using both MESH terms and free terms. Additional studies were obtained by reference tracking. This review was registered in PROSPERO, and the procedures foreseen by its statement were followed. Data were obtained from the included studies addressing the orthodontic mechanics, GCF sampling/handling methods,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…Considering the reported peak values at 24 hours in most studies such as those of Uematus et al, ( 20 ) Lee et al, ( 29 ) Ren et al, ( 24 ) and Karaduman et al ( 4 ), differences between our results and those of previous studies may be attributed to the time-dependent concentration of pro-inflammatory cytokines ( 21 ). Regarding the levels of cytokine in GCF over time, the most commonly reported results were peak levels of cytokines at one day after orthodontic force, regardless of treatment mechanics ( 30 ), thus a one-hour time period after load application is not long enough for release of a significant amount of pro-inflammatory cytokines into the GCF, and insignificant change in the level of these cytokines at one hour was expected in our study. On the other hand, insignificant increase in level of these cytokines in study teeth (compared to controls) at one hour (compared to baseline) indicates that chemotactic activity rapidly increases after mechanical load application ( 17 ).…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Considering the reported peak values at 24 hours in most studies such as those of Uematus et al, ( 20 ) Lee et al, ( 29 ) Ren et al, ( 24 ) and Karaduman et al ( 4 ), differences between our results and those of previous studies may be attributed to the time-dependent concentration of pro-inflammatory cytokines ( 21 ). Regarding the levels of cytokine in GCF over time, the most commonly reported results were peak levels of cytokines at one day after orthodontic force, regardless of treatment mechanics ( 30 ), thus a one-hour time period after load application is not long enough for release of a significant amount of pro-inflammatory cytokines into the GCF, and insignificant change in the level of these cytokines at one hour was expected in our study. On the other hand, insignificant increase in level of these cytokines in study teeth (compared to controls) at one hour (compared to baseline) indicates that chemotactic activity rapidly increases after mechanical load application ( 17 ).…”
Section: Discussionsupporting
confidence: 47%
“…It can only be concluded that cytokine levels in GCF may not be indicative of periodontal remodeling in pressure and tension. It has been suggested that the cellular response may be part of the overall increase in metabolic activity, not responding to mechanical stress ( 30 ). Thus, the level of cytokines cannot be well differentiated at the pressure and tension sites, and collection of GCF from the mesial and distal sides alone cannot serve as a suitable indictor for assessment of activity at the pressure and tension sites.…”
Section: Discussionmentioning
confidence: 99%
“…IL-1β is also a PGE inducer and, along with mechanical stress, synergistically regulates the formation of PGs in periodontal cells [26]. The levels of IL-1β and PGE2 are higher in the tension zones compared to compression zones, which supports the hypothesis that during the initial stage of orthodontic treatment, this cytokine would originate from osteoclasts in response to mechanical stress [27].…”
Section: Orthodontic Influencesmentioning
confidence: 59%
“…Finally, the information revealed significant interindividual changes in biological reactions to a force that led to a challenging comparison between diverse studies. However, according to the previous systematic review on force magnitude connected with the OTM procedure [36][37][38], similar problems had been experienced [38].…”
Section: Discussionmentioning
confidence: 70%
“…In this review, it appeared that hyalinization in rats had occurred before the test phase compared with other species. In one other study, details showed that the alveolar bone in rats had a better thickness than that of humans [36]. It seemed that the osteoid layer alongside the bone surface was less inexhaustible in rats compared with humans, justifying quicker hyalinization.…”
Section: Discussionmentioning
confidence: 96%